2017
DOI: 10.1155/2017/7420738
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Activities of Daily Living and Readmission within 90 Days in Hospitalized Elderly Patients with Heart Failure

Abstract: Aims To examine the relationship between activities of daily living (ADL) and readmission within 90 days and assess the cutoff value of ADL to predict readmission in hospitalized elderly patients with heart failure (HF). Methods This cohort study comprised 589 consecutive patients with HF aged ≥65 years, who underwent cardiac rehabilitation from May 2012 to May 2016 and were discharged home. We investigated patients' characteristics, basic attributes, and ADL (motor and cognitive Functional Independence Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…Anemia in HF patients is another possible predictor of readmission within 90 days [7,24]. In addition, low ADL and a low GNRI score were reported as features of a readmission group with heart disease [19,23]. Taken together, although the subjects of the present study had a relatively low rate of hospital readmission, they did show several characteristics related to readmission within 90 days.…”
Section: Characteristics Of Readmission Group Of Elderly Hf Patientsmentioning
confidence: 52%
See 3 more Smart Citations
“…Anemia in HF patients is another possible predictor of readmission within 90 days [7,24]. In addition, low ADL and a low GNRI score were reported as features of a readmission group with heart disease [19,23]. Taken together, although the subjects of the present study had a relatively low rate of hospital readmission, they did show several characteristics related to readmission within 90 days.…”
Section: Characteristics Of Readmission Group Of Elderly Hf Patientsmentioning
confidence: 52%
“…The Cox proportional hazard model in the present study identified these factors as predictors of hospital readmission. Low motor FIM scores (<75 points) at discharge in hospitalized elderly patients with HF was reported to be a predictor of readmission within 90 days in a previous study [23]. Also, the motor FIM score at discharge in hospitalized HF patients undergoing rehabilitation is reported to be 60 to 70 points, and the total FIM score is 90 to 100 points [29,30].…”
Section: Motor Adl and Gnri As Factors Of Hospital Readmissionmentioning
confidence: 82%
See 2 more Smart Citations
“…[33] Moreover, anxiety, appetite and sleep were confirmed to be predictors of readmission for CHF in retrospective studies, which may have been impacted by the fact that the patient's status influences the risk of readmission. [34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF.…”
Section: Discussionmentioning
confidence: 74%